Profesionalisme Jurnalis Dalam Film The Bang-Bang Club (Studi Analisis Semiotika Ferdinand De Saussure) - Revaldo Dewa Fransisko; Indrawati; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
One of the definitions of film is moving images. Movies are often grouped together under the umbrella term "cinema", which comes from the Greek word for motion, kinematics. There's a lot of different kinds of movie genres as well. A variety of genres, including but not limited to: acting, comedy, drama, thriller, and horror. The term "journalist professionalism" refers to a set of professional standards that are shared and recognized for journalists to be followed while working. Using Ferdinand De Sauussure's semiotic theory in relation to the signifier and signified in the film The Bang-bang Club, this study aims to understand how a professional journalist performs his duties both within and outside the scope of his work. Different by significant, consisting of the ideas, functions, and values transmitted by the signifier, the first is physically present and can be seen with the naked eye. Methods such as documentation studies, library studies, and online data searches are used for data collection. In the movie The Bang-bang Club, the protagonist serves as an object of analysis. Using six scenes from the movie The Bang-Bang Club, the object depicts the professionalism of film journalists.